Des inégalités garantes de la protection des Calanques ? - Valérie Deldrève; Arlette Hérat (VertigO)
The future National park of creeks, near an urban area of about two million inhabitants, is cause for numerous stakes connected to the nearness of the city. These issues are discussed in both arenas established by the Public Interest Grouping , and in those more spontaneous leaded by action groups of residents - local users, which practices and their necessary implication are recognized by the new law on parks (on 2006). Our aim is to show how the plural forms of environmental inequalities are linked to the development of claims in terms of nature conservancy. Neither the national park peri-urban dimension, nor its welcoming task allowed expression of concerns about access equality or the opening of these areas to the public. The shadowing of this peri-urban phenomena and even its assimilation to its only negative impact on the environment (too many visitors or damaging behaviour, pollutions), explain it largely, as well as the legitimation absence of the largest number of users ("non-traditional" and " worthless "). In order to complete our answer and to better highlight the articulation between city and nature in the park project, we focus then on the special case of “La Cayolle” district, recognized as the gateway of the inhabited “Sormiou creek” (cottages). The interactions between preservation policy and urban requalification strategy are visible. However, the questions in terms of equalities were avoided. This did not allow to the park to be a social development catalyst for the district.